The product-related failures in restaurants - Chan, Wei Leong; Wan Hassan, Wan Melissa; Boo, Huey Chern (Elsevier, 2014)
The foodservice industry in Malaysia is booming. While its contribution to the national economy is promising on one hand, the rivalry between the players amplifies on the other hand. This double-edged sword is promising yet challenging for industry practitioners. It certainly demands a fair standard of both the tangible products and intangible service to warrant a competitive edge. Previous studies have extensively looked into the facet of service in the restaurant setting, leaving the product aspect largely unaddressed. Particularly, identifying and categorizing the product failures in restaurants are lacking. Therefore, this study was conducted to bridge the gap. Online complaint data from January 2010 to August 2011 were sourced from two local chained-restaurant companies. A total of 450 usable complaint cases were gathered. Content analysis yielded three major categories, namely sensory quality, safety quality, and others. Among these, sensory quality was the main cause of dissatisfaction. The categorization entails noteworthy implications to researchers and industry practitioners.